Educated Parents’ Practice of Child Labour in Ekiti State, Nigeria - Oluwagbohunmi, Margaret F.; Popoola, Esther O. (European Scientific Journal, ESJ, 2023)
Child labour has been observed to be a common practice among illiterates due to poor socio-economic background. Some parents and guardians keep their children in child labour in order to supplement family income. Educated parents who should know the risks involved and enlighten the illiterate parents seem to engage children in hazardous work that directly endangers their health and moral development. This paper examined educated parents’ practice of child labour in Ekiti state. Descriptive survey research design was adopted with a sample of 600 educated parents selected among civil servants working in Local Government Secretariats through multi stage sampling procedure. One research question and three hypotheses were generated for the study. A questionnaire tagged “Educated Parents’ Practice of Child Labour Questionnaire (EPPCLQ)” was used to collect data. The instrument was subjected to screening by experts to ensure validity and reliability was determined through test re-test method that yielded 0.85 reliability coefficients. The study revealed that level of child labour practice among educated parents was moderate, practice of child labour differed based on gender and location of educated parents while the study found no significant difference in educated parents’ practice of child labour based on income. Based on this, it was recommended among others that parents should desist from engaging children in child labour which has been found to be injurious and detrimental to their health and moral development and families need to look for other means of sourcing for income in order to fight poverty and discourage the practice.